Dynamic symmetrical mode III interface crack issues between unalike materials. Issue 3 (17th June 2019) - Lu, Nianchun; Xiang, Qian; Hao, Guodong; Wang, Yuntao
Abstract : Using the theory of complex variable functions, analytical solutions for dynamic symmetrical mode III interface cracks of two unalike materials were investigated. The issues considered could be very easily translated into Riemann–Hilbert problems according to the methods of self-similar functions, and analytical solutions of the stresses, displacements and dynamic stress intensity factors for the edges of symmetrical mode III interface cracks subjected to moving enhancive loadings, Pt 6 / x 6 and Px 7 / t 6, were obtained. The solutions were obtained by application of the superposition principle. The solutions of discretionally intricate queries could be readily acquired.